Antibacterial Activities and Characterization of Novel Inhibitors of LpxC - Clements, John M. (American Society for Microbiology, 2002)
Lipid A is the hydrophobic anchor of lipopolysaccharide (LPS) and forms the major lipid component of the outer monolayer of the outer membrane of gram-negative bacteria. Lipid A is required for bacterial growth and virulence, and inhibition of its biosynthesis is lethal to bacteria. UDP-3-O-(R-3-hydroxymyristoyl)-N-acetylglucosamine deacetylase (LpxC) is a metalloenzyme that catalyzes the second step in the biosynthesis of lipid A. Inhibitors of LpxC have previously been shown to have antibiotic activities. We have screened a metalloenzyme inhibitor library for antibacterial activities against an Escherichia coli strain with reduced LpxC activity. From this screen, a series of sulfonamide derivatives of the α-(R)-amino hydroxamic acids, exemplified by BB-78484 and BB-78485, have been identified as having potent inhibitory activities against LpxC in an in vitro assay. Leads from this series showed gram-negative selective activities against members of the Enterobacteriaceae, Serratia marcescens, Morganella morganii, Haemophilus influenzae, Moraxella catarrhalis, and Burkholderia cepacia. BB-78484 was bactericidal against E. coli, achieving 3-log killing in 4 h at a concentration 4 times above the MIC, as would be predicted for an inhibitor of lipid A biosynthesis. E. coli mutants with decreased susceptibility to BB-78484 were selected. Analysis of these mutants revealed that resistance arose as a consequence of mutations in the fabZ or lpxC genes. These data confirm the antibacterial target of BB-78484 and BB-78485 and validate LpxC as a target for gram-negative selective antibacterials.